The Communication of Timbral Intentions Between Pianists and Listeners and Its Dependence on Auditory-Visual Conditions - Li, Shen; Timmers, Renee; Wang, Weijun (Frontiers in Psychology, 2021)
The perceptual experiment reported in this article explored whether the communication of five pairs of timbral intentions (bright/dark, heavy/light, round/sharp, tense/relaxed, and dry/velvety) between pianists and listeners is reliable and the extent to which performers' gestures provide visual cues that influence the perceived timbre. Three pianists played three musical excerpts with 10 different timbral intentions (3 × 10 = 30 music stimuli) and 21 piano students were asked to rate perceived timbral qualities on both unipolar Likert scales and non-verbal sensory scales (shape, size, and brightness) under three modes (vision-alone, audio-alone, and audio-visual). The results revealed that nine of the timbral intentions were reliably communicated between the pianists and the listeners, except for the dark timbre. The communication of tense and relaxed timbres was improved by the visual conditions regardless of who is performing; for the rest, we found the individuality in each pianist's preference for using visual cues. The results also revealed a strong cross-modal association between timbre and shape. This study implies that the communication of piano timbre is not based on acoustic cues alone but relates to a shared understanding of sensorimotor experiences between the performers and the listeners.